A regulação urbanística e ambiental no contexto metropolitano: reflexões a partir do Vetor Norte da metrólpole belo-horizontina - Patricia Silva Gomes (2013)
This thesis aims to analyze the limits and possibilities of urban and environmental regulation of land parcels, within the context of the northern vector of the Belo Horizonte Metropolitan Region. If during the Fordist cycle the metropolitan region was characterized by the proliferation of precarious settlements (without basic infrastructure and other means of collective consumption), at present time it has had its dynamics of growth changed by the implementation of large projects with public resources. One consequence of this process has been the progressive deployment of new land subdivisions, some with complex design similar to real cities, seeking to appropriate land rent differentials arising from those investments. The regionis also characterized by natural frailties given the presence of a large karst territory and areas with tourist, cultural and landscape attractions, organized in conservation areas. The land subdivision activity is largely responsible for adding new areas to the urban tissue of the metropolis which, when closely examined, explicit the contradictions between the role of the State to provide the general conditions of production and urban-environmental regulation. The results obtained from a qualitatively and quantitatively constructed database show the coexistence of a environmental, social and urbanistic passive of previous decades with the proliferation of new land subdivisions, and shows the limits of the regulatory procedure adopted from a reflection of urban approval (municipal and metropolitan) and environmental. In the county context, for example, the division of the ground are inserted in the city with out the recovery of added value of land arising from large investments is incorporated, although these cities have prepared Master Plans in line with the Estatuto da Cidade (City Statute, Federal Law 10.257/2001) in which many of these urban instruments are provided. In the metropolitan context, the lack of metropolitan planning tools, materialized in a macrozoning proposed by the Integrated Development Plan of the Metropolitan Region of Belo Horizonte (PDDI-RMBH), prevents a more systematic evaluation of urban impacts from its implementation, prevailing specific formal approvals guided by the municipal logic. Within the environmental licensing, these processes show, on the one hand, a capitalization of natural attributes and a policy consensus (concealing conflicts) and, on the other hand, the (quasi)impossibility to grant environmental license to the parcelling go flow-income developments, thus restricted to urban and environmental regulation. A French approach, notably through the experience of planning and regulationof the metropolitan area of Lille, brings elements to weave possibilities in to this debate. In Brazil, the Bill 3057/2000 (revising the Federal Law of Land Subdivision, 6766/1979) opens a range of possibilities for regularization of land subdivisions and introduces the idea of the city of full management" (following the existing federal provisions). It is argued that these devices should be added to the operational issues to strengthen the Master Plans, the participatory tools and the municipal technical teams, in order to ensure "full management". In this thesis, this issue is organized around the idea of urban land responsibility.